The Influence of Business Competitiveness on Relocation Decisions - Bambang Dwi Suseno; Septiana Sari; Ahmad Maksum; Malik Fatoni (Universitas Negeri Semarang, 2022)
This study aims to examine the causal relationship between wage policy, business competitiveness, and employee productivity on the decision to relocate the company's operating base as a research problem. The research method used is a survey method with a correlational quantitative approach, and the sampling technique used is non-probability sampling with a purposive sampling method. This research uses structural-based variance equations, SmartPLS variance, and SEM-based. The population in this study are managers who work in the footwear industry in Banten Province. The test results show that (1) wage policies have a significant effect on employee productivity; (2) wage policies have a significant effect on business competitiveness; (3) wage policies have a significant effect on business relocation decisions; (4) employee productivity has no effect on business relocation decisions; and (5) business competitiveness has a significant effect on business relocation decisions. The theoretical implication is that the findings of this study contribute to the theory of human resource economics and business competitiveness. The managerial implication of the results of this study is the importance of formulating appropriate wage policies and increasing employee productivity so that there is no relocation of companies outside Banten Province.